Prenatal Nutritional Factors and Neurodevelopmental Disorders: A Narrative Review - Federica Cernigliaro; Andrea Santangelo; Rosaria Nardello; Salvatore Lo Cascio; Sofia D’Agostino; Edvige Correnti; Francesca Marchese; Renata Pitino; Silvia Valdese; Carmelo Rizzo; Vincenzo Raieli; Giuseppe Santangelo (Life, 2024)
According to the DSM-5, neurodevelopmental disorders represent a group of heterogeneous conditions, with onset during the developmental period, characterized by an alteration of communication and social skills, learning, adaptive behavior, executive functions, and psychomotor skills. These deficits determine an impairment of personal, social, scholastic, or occupational functioning. Neurodevelopmental disorders are characterized by an increased incidence and a multifactorial etiology, including genetic and environmental components. Data largely explain the role of genetic and environmental factors, also through epigenetic modifications such as DNA methylation and miRNA. Despite genetic factors, nutritional factors also play a significant role in the pathophysiology of these disorders, both in the prenatal and postnatal period, underscoring that the control of modifiable factors could decrease the incidence of neurodevelopmental disorders. The preventive role of nutrition is widely studied as regards many chronic diseases, such as diabetes, hypertension, and cancer, but actually we also know the effects of nutrition on embryonic brain development and the influence of prenatal and preconceptional nutrition in predisposition to various pathologies. These factors are not limited only to a correct caloric intake and a good BMI, but rather to an adequate and balanced intake of macro and micronutrients, the type of diet, and other elements such as exposure to heavy metals. This review represents an analysis of the literature as regards the physiopathological mechanisms by which food influences our state of health, especially in the age of development (from birth to adolescence), through prenatal and preconceptional changes, underlying how controlling these nutritional factors should improve mothers’ nutritional state to significantly reduce the risk of neurodevelopmental disorders in offspring. We searched key words such as “maternal nutrition and neurodevelopmental disorders” on Pubmed and Google Scholar, selecting the main reviews and excluding individual cases. Therefore, nutrigenetics and nutrigenomics teach us the importance of personalized nutrition for good health. So future perspectives may include well-established reference values in order to determine the correct nutritional intake of mothers through food and integration.